Occurrence of SARS-CoV-2 infection among healthcare personnel: results from an early systematic review and meta-analysis. - Riccò, Matteo; Gualerzi, Giovanni; Ranzieri, Silvia; Peruzzi, Simona; Valente, Marina; Marchesi, Federico; Bragazzi, Nicola Luigi; Signorelli, Carlo (Acta Biomedica Atenei Parmensis, 2021)
Background. SARS-CoV-2 infection has become a global public health concern globally. Even though Healthcare Workers (HCWs) are supposedly at increased risk for SARS-CoV-2 infection, to date no pooled evidence has been collected.Materials and Methods. We searched online electronic databases (PubMed, Embase, medRxiv.org for pre-prints) for all available contribution (up to May 20, 2019). Two Authors independently screened articles and extracted the data. The pooled prevalence of SARS-CoV-2 was analyzed using the random-effects model. The possible sources of heterogeneity were analyzed through subgroup analysis, and meta-regression.Results. The overall pooled prevalence of SARS-CoV-2 was 3.5% (95%CI 1.8–6.6) for studies based on molecular assays, 5.5% (95%CI 2.1–14.1) for studies based on serological assays, and 6.5% (95%CI 2.5–15.6) for point-of-care capillary blood tests. Among subgroups, serological tests identified higher risk for SARS-CoV-2 seropositivity in physicians than in nurses (OR 1.436, 95%CI 1.026 to 2.008). Regression analysis indicated the possible presence of publication bias only for molecular tests (t -3.3526, p-value 0.002648).Conclusions. The overall pooled prevalence of SARS-CoV-2 was lower than previously expected, but available studies were affected by significant heterogeneity, and the molecular studies by significant publication bias. Therefore, further high-quality research in the field is warranted.